Avaliação microestrutural via EBSD das zonas parcialmente diluídas em revestimentos dissimilares de Aços ASTM A36 com as Ligas AWS E 309L e AWS ER NiCrMo-3 depositadas pelo processo MIG em camada única e dupla - Silva, William Constantino da (2023)
Oil exploration in ultra-deep waters has intensified with the discovery of the pre-salt layer. Given this scenario, the development and improvement of materials and engineering components become essential to face the new challenges of this sector. In particular, a service life and corrosion resistance of components and structures must be improved. To achieve this goal, several initiatives have used resistance cladding of alloys with special properties, such as stainless and nickel alloys, on resistant steels. However, dissimilar pain can generate problems, such as the formation of discontinuous regions of high hardness in the interfacial region, known as Partially Diluted Zones (PDZ). In this sense, a study was followed using metallic alloys of high corrosion resistance. The technique of Electron Microscopy by Backscattered Electron Diffraction (EBSD) was used to characterize these interfacial regions and safely and deeply evaluate the microstructure of the claddings produced. For the work, welding electrode from alloys AWS E 309L and AWS ER NiCrMo-3 — stainless 309L and Inconel 625 — are used as filler metals deposited on ASTM A36 steel test plates. Automated single and double layer MIG interface were employed. The metallurgical-mechanical characteristics were evaluated by means of Field Emission Scanning Electron Microscopy (FEG-SEM) using the technique of Backscattered Electron Diffraction (EBSD), Energy Dispersive X-Ray Spectroscopy (SEM-EDS) and Vickers Microhardness. The results appreciated that the Heat Affected Zone (HAZ) had its microstructure modified and, consequently, its microhardness directly related to the cladding deposition mode (single or double layer). Regarding the PDZs, they were observed in different morphologies such as beaches, swirl, and islands, with high percentages of iron, chromium, and nickel, along with high microhardness values and a microstructure typically characteristic of martensitic structures. When comparing microhardness percentages between single-layer and double-layer deposition, it was found that doublelayer deposition was more beneficial in significantly reducing microhardness values in the PDZs and in the HAZs of the coated components.